Critiquing coloniality, 'epistemic violence' and western hegemony in comparative education – the dangers of ahistoricism and positionality. Issue 2 (2nd April 2020) - Vickers, Edward
ABSTRACT: Claims regarding Western neo-colonial domination over scholarship in Comparative and International Education (CIE) have recently commanded much attention – for example in a 2017 special issue of the journal Comparative Education Review (CER) on the theme of 'contesting coloniality.' Stressing their marginal 'positionality, ' the contributors to that special issue relate their critique to a narrative of 'epistemic violence' seen as underpinning 'Western' or 'Northern' hegemony in the CIE field and beyond. Adopting a historical perspective, I argue here that positing a dichotomy between a colonialist 'Western modernity' and a uniformly victimised 'non-West' is empirically unsustainable, and involves its advocates in propagating just the kind of essentialism and Eurocentrism that they condemn. I also argue that the centrality of 'positionality' and 'opacity' in postcolonialist or decolonial arguments, as expounded in the CER special issue, impedes meaningful and constructive scholarly dialogue. Scholarship in this vein threatens to divide the CIE field, undermine its wider credibility and distract from analysis of the pressing problems that confront us today. Comparativists need to balance critical scholarship concerning the implications of 'colonialism' with greater attention to the comparative study of its history.